Human Resource Practices and Innovation Capability through Employee Engagement and Organizational Learning - Agus Rohmat Hidayat; Agis Ahmad Rodiansjah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
This comprehensive study examines the complex relationship between human resource practices and innovation capability, with employee engagement and organizational learning as critical mediating variables. Conducted in the Indonesian business context with 385 respondents from manufacturing and service companies, this research uses Structural Equation Modeling (SEM) to analyze how HR investments translate into innovation outcomes. Results show HR practices significantly enhance innovation capability through direct effects (?=0.382, p<0.001), indirect effects via employee engagement (?=0.209, 95% CI [0.156, 0.268]), and organizational learning (?=0.173, 95% CI [0.125, 0.227]). The model explains 68.4% variance in innovation capability (R²=0.684). Findings extend Resource-Based View, Social Exchange Theory, and Organizational Learning Theory while providing practical guidance for optimizing HR strategies.